Vitaherb (perencanaan pengembangan usaha jamu) - andriansyah, Sigit indra; Cholid, Idham (Publikasi Riset Mahasiswa Manajemen, 2024)
Vitaherb is a business operating in the culinary sector that produces and sells herbal drinks. This business offers 3 flavor choise, namely Sour Turmeric, Basil Sour Turmeric, and Saffron Colored Rise. This business is located at Letnan TNI Dr. Ibnu Sutowo street, number 3, Alang-Alang Lebar District, Palembang, South Sumatera 30151. The reason for choosing this business is because there are no herbal drink shop in the Springhil area. Promotion will be carried out using online media and brochures. Based on the business feasibility aspect, Vitaherb is declared feasible top run and has profitable prospect in the future